The Effect of Site Class, Tree-age and Axial Direction on Adhesion Properties of Teakwood - Tibertius Agus Prayitno; Yustinus Suranto; Rieska Wahyu Indra Pratama; Dasta Dasta (Masyarakat Peneliti Kayu Indonesia, 2013)
Teak wood is a well-known prime wood species in Indonesia. The teak forest had been managed well by PERHUTANI, a state forest company for a long time. In the teak forest the site quality has been classified according to land’s capability to grow the teak plant. This site classification had been set up from the beginning of forest management and it has not been reviewed yet. This research’s objectives are to know the effect of teak forest site quality class and axial direction on the adhesion properties of the teak wood. The research conducted using Completely Randomized Design arranged in factorial experiment. The first experiment used site quality and axial direction factors, while the second experiment used tree’s age and axial direction. The site quality factor consisted of three levels of site index III, III/IV and IV. The three levels of axial direction of the teak stem were butt, center and top. The tree’s age consisted of three age class of 25, 35 and 45 years. Three teak trees employed as replication. The adhesion properties parameter were wood specific gravity, adhesion compression shear test and wood failure in both dry and wet condition using block test. The first research result showed that no interaction factor affected in adhesion properties. The teak growing site-class influenced significantly to the wood specific gravity and adhesion shear strength. The more fertile of teak growing site class, the lower wood specific gravity and adhesion strength. The site class of III, III/IV and IV revealed the average wood’s specific gravity of 0.54; 0.50 and 0.47 consecutively. The adhesion strength produced from the three site classes were 41.71; 32.56 and 23.52 kg/cm2 consecutively. The axial direction (from the butt to the top) showed a decreasing trend of wood specific gravity and adhesion strength. The second research showed that tree age affected significantly the wood specific gravity. The wood specific gravity increased from 0.57 to 0.67 and 0.69 produced from tree age of 25, 35 and 45 year old consecutively.